Dose-dense intensified sequential versus conventionally-dosed anthracycline and taxane-containing neoadjuvant therapy in patients with inflammatory breast cancer - Ditsch, Nina; Toth, Bettina (Anticancer research, 2012)
Background: This post-hoc analysis aimed to compare an intense dose-dense sequential chemotherapy (DD-CT) and a conventionally-dosed chemotherapy (CD-CT) in the neoadjuvant AGO-1 study, focusing on the subgroup with inflammatory breast cancer (IBC). Patients and Methods: Out of 668 randomised patients, 101 patients presented with IBC. Patients received epirubicin followed by paclitaxel every 2 weeks (DD-CT) or simultaneously every 3 weeks (CD-CT). Results: No differences in pathological complete response rates were observed [odds ratio (OR)=1.27, p=0.33]. Most patients were scheduled for mastectomy before starting therapy; however, in 21.7% breast-conserving surgery was performed. Disease-free survival rates [Hazard Ratio (HR)=0.65; p=0.597] and overall survival rates (HR=1.40; p=0.327) were similar for both treatment arms. Patients with breast-conserving surgery had a significantly better outcome than patients treated with mastectomy (disease-free survival: HR=0.41; p=0.034 and overall survival: HR=0.09; p=0.003). Conclusion: Patients with IBC benefited not from DD-CT but from breast-conserving surgery after neoadjuvant chemotherapy.